Work programme 2014 - (:unkn) unknown (Publications Office of the European Union, 2014)
"Cedefop's work programme 2014 is consistent with its medium-term priorities, its mission as laid down in the founding regulation and the European policy context, which is described in greater detail in Chapter 2. Chapters 3 to 5 describe planned activities by medium-term priority, Chapter 6 summarises the various communication activities and Chapter 7 refers to management and administrative issues. Results of the 2014 risk assessment and activities included in the risk management plan 2014 are presented in Chapter 8. The work programme concludes with Chapter 9 which contains a detailed description of activities and projects in tabular form. Several annexes provide detailed background information and ovierviews." (Editor, BIBB-Doku)
Keywords: S 3.5.5.1 CEDEFOP; S 2.3 Berufsbildungspolitik; CEDEFOP; Programm; Berufsbildung; Förderung; Internationale Zusammenarbeit; Berufsbildungspolitik; Europäische Union